DESAIN MODEL PRAKTIKUM IPA BERBASIS JAS (JELAJAH ALAM SEKITAR) DI SEKOLAH DASAR SE-KECAMATAN BENDOSARI - Dwi Anggraeni Siwi; Nurratri Kurnia Sari; Koko Prasetya (Premiere Educandum : Jurnal Pendidikan Dasar dan Pembelajaran, 2016)
The purpose of this study are 1) describe of the initial conditions of the practicum in a Primary School District of  Bendosari to improve the understanding of  the material and activate learners’ understanding; 2) The design prototype model of  lab-based science JAS applied in a Primary School District of Bendosari; 3) The final form of the model design lab-based science JAS applied in a Primary School District of  Bendosari. This research is the development, conducted in sub-district elementary Bendosari Festive Year 2015/2016. In this research, the techniques were the development of needs analysis and design study model. The results in this study are the 1) Initial Condition form of characteristic learning model integrative who can not equip students in the control and learning science is: a model that contains the syntax: Mastery of  the science material and mastery of  practical science-based tracking the nature (JAS). 2) The initial design of  models of lab-based science tracking the nature (JAS) in the form of a syllabus, lesson plans, and worksheets. 3) In the vote on the model validator lab stated that lab model design based science used tracking the nature (JAS) can be used through the revision stage.Keywords: Practicum, Natural Sciences, JAS (Roaming Neighborhood Nature)